Information technology governance on audit technology performance among Malaysian public sector auditors - Veerankutty, Farida (MDPI, 2018)
The concept of Industry 4.0 has considerably altered the way organisations operate and has impacted every aspect of life. Furthermore, the fast-growing trend of information technology (IT) transformation in organisations and huge IT investment by Malaysian government have triggered the significance of IT risk and its related controls. Besides, technology-enabled auditing and IT-oriented audit procedures have become crucial when performing audit tasks in an electronic environment. Although many initiatives are being implemented to improve technology usage, audit technology use among auditors is still low and auditors are not attaining sufficient progress in the use of technology. This implies the current strategies and policies may not effectively support technology implementation. In the same vein, the under-utilisation of technologies was reported due to inadequate governance. Thus, this study intends to investigate the impact of IT governance on audit technology performance. IT governance is a mechanism to stimulate anticipated behavior in the use of technology among the employees of an organisation. Surveys using closed-ended questionnaires were distributed to approximately 309 Malaysia public sector auditors. The results show that IT governance mechanisms such as IT strategy and management support significantly influence the audit technology performance. IT governance does play a significant role in assuring the successful utilisation of audit technology.